GAMIFICATION OF DUOLINGO IN RISING STUDENT’S ENGLISH LANGUAGE LEARNING MOTIVATION (Jurnal Bahasa Lingua Scientia, 2021)
This study aims to identify students' motivation in learning English through the Duolingo application, its effects, and what makes it different from conventional learning. The Duolingo application is free language acquisition and education for the world. The term acquisition itself is interpreted differently by language researchers. Some researchers distinguish between obtaining and learning. On the other hand, other researchers consider the term to be the same. In this study, researchers refer to the idea that they are the same. In conducting this research, researchers used case studies to analyze data. The researchers were selected five students of second-grade SMK Ngunut 1 Tulungagung who play of Duolingo application to get their second language motivation. Data was collected by direct observation and in-depth interviews with subjects who had two learning language experiences such as books and learning applications. The reason why choosing games as a factor in improving English learning in this study is because games have become one of the results of the development of popular technology in the community.
Keywords: english foreign language; learning motivation; gamification